Multipurpose handle stabilizer – to help you handle your life / Nur Athilla Alimin ... [et al.] - Alimin, Nur Athilla; Zainudin, Nur Hadirah Faqihah; Suhairi, Siti Nadiah Afiqah; Rumpungan Jr, Joseph Joshua; Aziz, Adrianna (2021)
Hand tremors or shaky hands from mild to severe can affect anyone and have impacts on daily activities which cause struggles in writing, drawing, and handling tools or utensils. Hand tremors can be caused by a number of reasons but commonly caused by neurological conditions such as Multiple Sclerosis (MS), traumatic brain injury, or Parkinson's disease. A report by the Department of Statistics Malaysia in 2018 stated that the number of patients with Parkinson's disease is expected to increase by five times from the current approximate 20,000 to 120,000 by 2040. The Multipurpose Handle Stabilizer product aims to help people with mild to severe shaking hands in their daily activities. It focuses on assisting affected people in holding and using tools with handles and intending to make their life more convenient. Currently, products with stabilizing features on the market are only focused on cameras and detachable eating utensils whereas our product intends to be more multipurpose which adds convenience and is more efficient. The specialty of our product is that it features non-detachable utensil handle head with size adjustable opening to ensure that it is suitable to be used with any type and size of handles; it is also equipped with flashlight and stabilizing tech as well as a long-lasting rechargeable battery. This product would be able to assist those affected with hand tremors and their caregivers as this product gives them the ability to hold tools such as kitchen utensils, makeup brushes, and stationaries. This product’s innovative feature is it is straightforward and easy to use; any tools that wished to be used can directly be inserted into the Multipurpose Handle Stabilizer. With this product, victims of hand tremors and neurological conditions can gain confidence in being more independent and carrying out their daily activities from applying makeup on their own to cooking simple meals.